Oral English is Oral and I am Deaf: Deaf and Hard of Hearing on Trial Phonetics and Phonology In Nigeria - Olubukola Abiodun Olufemi-Adeniyi; Olaotan Oladele Kuku; Samuel Olufemi Adeniyi (UNIB Press, 2024)
Speaking is about hearing and inability to hear or hear correctly may hamper the expected communication of meaningful words. For the deaf and hard of hearing, production of meaningful sound becomes difficult because of inability to process auditory information properly. Hence, engagement in exercise that will involve oral language might be a difficult task. This study therefore investigated the attitudes to and knowledge of oral English by the deaf and hard of hearing learners and their teachers’ perception. Descriptive survey research design was employed and a total of 100 deaf and hard of hearing students and 29 teachers were purposively selected. Attitudes to Oral English Scale, Perceived Knowledge of Oral English and Perceived Adequacy of Oral English with reliability of 0.78, 0.81, and 0.77 respectively were the instruments used to collect relevant data. Data collected were analysed using simple descriptive statistic such as percentage and Pearson Product Moment Correlation. The results revealed that deaf and hard-of-hearing students have positive attitudes towards the English language but possess poor knowledge of oral English and exhibit a negative disposition towards the teaching of oral English to the deaf and hard-of-hearing. Additionally, there was no significant relationship between their attitudes towards oral English and their knowledge of oral English. Hence, alternative arrangement should be provided for the deaf and hard of hearing to compensate for the oral English learning.